Faktor-Faktor yang Mempengaruhi Ketidakteraturan Berobat Penderita Kusta di Kabupaten Blora - Henny Indriyanti, Hardyanto Soebono, Suharyanto Supardi (Berita Kedokteran Masyarakat (BKM), 2003)
Bakcground: Leprosy continues to remain public health problem particularly in developing countries. Treatment is the most important aspect in leprosy control, however as the long duration of treatment compliance is critical point to success of therapy.Objective: Determine how big the problem of treatment compliance og leprosy patients in Kabupaten Blora and what factors influencing the compliance of those patients. A case control study was conducted in 22 health centers involving 126 leprosy patients. Patients who took irregularly Multi Drug Therappy (MDT) and heve been Released From Treatment (RFT) were considered as the case. Whereas those who regularly took MDT were considered as the control. Various variables observed from the patients, treatment and health providers were analysed using bivariate as well as multivariate statistical methods.Results: Showed that by using bivariate analysis dominant factors of irregular treatment of the patient to MDT in Kabupaten Blora were low social economy (odds ratio/OR:2,69), low knowledge on leprosy (OR:2,89), side effect of the drugs (OR:6,22), leprosy reaction (OR:3,43), disabilies (OR:4,2), no health education (OR: 13,12) and no home visit of provider (OR: 2,79). However, by multivariate log regression only 2 variables i.e. no health education and side effect of drugs were significantly influencing the irregularity to treatment. Nosignificant correlation between sex, education, detection methods, distance of health services, leprosy type, supervison and patient perception and the irregular treatment were found.Conclusion: That no health education and side effect of drugs are significant factors of irregularity to treatment in leprosy. Keywords: Leprosy-MDT-irregular treatment-health education-side effect of drugs